Integrating Islamic Parenting and Assertive Training in Students’ Character and Learning Motivation - Achadah, Alif; Putri, Wulan Antira; Miftakhi, Diah Rina; Munzir; Ikhwan, Aisyah Nuril (LETIGES, 2026)
The phenomenon of low self-confidence, communication difficulties, and decreased learning motivation of students at the Darul Madinah Tahfidzul Qur'an Islamic Boarding School indicates the need for a parenting approach that is not only normative-religious but also responsive to the psychological needs of students. This study aims to examine in depth the practice of parenting in the Tahfidz Islamic boarding school in integrating Islamic parenting values with assertiveness training techniques, and analyse its implications for the formation of character and learning motivation of students. This study uses a descriptive qualitative approach with a case study design. Primary data sources were obtained from four main informants, namely the head of student care, the head of the foundation, the (GPH:Guru Pembina Harian) supervisor for worship, the GPH supervisor for ta'lim, and several students as supporting informants. Meanwhile, secondary data were obtained through documentation of the coaching program, activity log reports, and tahfidz reports. Data collection was carried out through semi-structured interviews, participant observation, and documentation. Data analysis used an interactive model that includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source and technique triangulation, member checking, and audit trail. The results of the study indicate that the integration of Islamic parenting based on the values of monotheism, faith, morals, and habituation with assertiveness training techniques has been proven to significantly strengthen the character of responsibility, self-confidence, good communication quality, and increased learning motivation of students. Theoretically, these findings strengthen Bandura's social learning theory and Lickona's character education and expand the study of Islamic education through a holistic and dialogical parenting approach. This study confirms that the integration of Islamic values and assertiveness is an effective parenting strategy in Islamic boarding schools. The formulation of an integrated parenting model that combines Islamic values and assertiveness techniques can be a positive, applicable, and contextual contribution to educational institutions. However, the limitations of this study in the context of a single Islamic boarding school mean that the findings cannot be generalised widely.